Self-scheduling of wind power generation with direct load control demand response as a virtual power plant - Tahmasebi M.; Pasupuleti J. (2023)
A virtual power plant, VPP, defined as a collection of dispersed generator units, storages and controllable load systems aggregated as a unique power plant. VPPs were categorized as Commercial virtual power plant, CVPP and Technical virtual power plant, TVPP. CVPP was related to the market and expected to obtain a maximum benefit from the generation and demand portfolio. The TVPP takes into consideration the operation of the grid and expected to solve possible contingencies. Two technologies that could be offered as a CVPP were wind power producer, WPP, and Flexible consumption especially direct load control, DLC, demand response program. This work focused on the economic operation of CVPP consisting of WPP and DLC in a competitive electricity market and the WPP intermittent compensation. The researcher in this paper used self-scheduling, SS, method to derive maximum expected profit from the Energy Markets. The problem of self- scheduling of the CVPP was formulated and solved by GAMS software. The case study and numerical results were presented in this paper.